A Theoretical Model of Intergenerational Tutoring: Advancing the Field. Issue 1 (2nd January 2020) - Topping, Keith J
ABSTRACT: This paper presents a psychological model of intergenerational tutoring, which applies to both helpers and those who are helped. It shows how fully formed intergenerational tutoring can operate, and can thus identify gaps. These gaps can be addressed and some filled by learning partners, perhaps with help from professionals or more experienced partners. Sixteen elements are identified, the first two in sequence, then five with equal weight, then nine in sequence. The model is a template for monitoring intergenerational interactions as they are happening. It also forms a tool for self-assessment/peer assessment. Additionally, it may help in designing intergenerational tutoring.